Regime consolidation through transitional justice in Europe: the cases of Germany, Spain and Turkey - Mihr, Anja (International journal of transitional justice, 2017)
Transitional justice (TJ) measures in post-Second World War Europe illustrate how they consolidate political regimes in both autocratic and democratic ways. TJ measures can work as catalysts during transition (regime change) and transformation (regime consolidation) periods to help build either exclusive autocratic societies or inclusive democratic ones. In this article I look at how policy makers use TJ measures such as trials, reparations, vetting procedures and even amnesty laws and memorials to, on the one hand, establish an exclusive and thus selective bias and often arbitrary political regimes and, on the other hand, establish an inclusive, diverse and pluralistic political regime. I test how TJ measures as independent variables correlate with institution building after the end of dictatorships or conflict and thus impact on political regime consolidation as the dependent variable in the cases of postwar Germany, post-dictatorial Spain and Turkey in the second half of the 20th century.